The technology of producing sorbents from linseed flax shive - E. M. Puchkov; A. V. Galkin; I. V. Ushchapovsky (Аграрная наука Евро-Северо-Востока, 2019)
Flax processing waste, flax shive is of great importance for producing sorbents from non-wooden materials in Russia. There are more than 700 thousand hectares of linseed flax crops in the country. Linseed flax shive had been burned everywhere until recently as there was no technology of its processing. The waste disposal problem in the linseed flax cultivation regions could be solved by introducing new flax waste recycling and linen producing technologies developed by scientists of the Federal Research Center for Bast Fiber Crops. In 2015-2018 some studies were carried out in research laboratories and on the experi-mental plant of the center as well as on flax-sowing farms of the Udmurt Republic, Rostov region and Krasnodar territory. The research has shown that linseed shive contains 49-51% of cellulose and 23-27% of lignin, on which the sorption capacity of the material depends. The values of flax waste sorbent sorption capacity by the effective sorption of ions in relation to heavy metals are 85-91 %, to oil products - from 3.9 to 17.3 mg/g, to iodine and methylene blue - 222 and 220 mg/g, respectively. These values don’t concede the sorbents from wood and can replace the use of the latter. The developed technology of obtaining sorbent from flax allows to organize the production directly on flax-sowing farms and flax factories applying raw materials ready to use.